Elaboration of 4′-Phosphopantetheine Adenylyltransferase inhibitors and Benzoxaboroles as antimalarial agents - Morake, Mokhitli (Department of Chemistry, 2023)
Malaria continues to be one of the leading causes of morbidity and mortality in the impoverished parts of the world with majority of the disease burden in Sub-Saharan Africa. The World Health Organization (WHO) 2021 report estimates at least 241 million cases and 627 000 deaths due to malaria in 2020. This is an increase compared to 2019 (227 million cases and 558 000 deaths), and it is also attributed to plateaued declines in malaria cases since 2015 and the 2020 COVID-19 pandemic. The WHO African region accounts for about 95% of the cases, and the mortality in children under 5 years of age is still alarmingly high. Further complicating the situation is the rise in drug-resistant species of the causative agent of the most lethal malaria, Plasmodium falciparum (P. falciparum). P. falciparum has developed resistance against almost all clinically used antimalarials, and there are mounting reports of resistance to artemisinins which are currently the most commonly used antimalarials. Artemisinins are fast-acting and are coupled with longer-acting partner drugs in artemisinin combination therapy (ACT). In South-East Asia, slow parasite clearances and high recrudescence rates following ACT have been reported and resistance to artemisinin partner drugs have been established. Resistance markers to artemisinins have also been identified even in Africa. Therefore, novel antimalarials with better activity against resistant parasites not quickly prone to rapid resistance development are urgently needed. These drugs must have novel modes of actions and act against novel targets in the parasite. To that end, this PhD project explored novel scaffolds on which to base future antimalarial drug discovery projects. A 500-member compound library of the bacterial 4′-Phosphopantetheine adenylyltransferase (PPAT) inhibitors obtained from AstraZeneca (AZ) containing two chemical series, viz. Ugi and cyclohexyl pyrimidine series, was subjected to the medium-throughput screening at the University of Cape Town (UCT)'s Holistic Drug Discovery and Development Centre (H3D). PPAT is a previously unexplored target in P. falciparum, and the current study aimed to reposition both the target and the bacterial PPAT inhibitors for malaria. As such, four hits (two from each series) with moderate antiplasmodium activity against the drugsensitive PfNF54 strain with IC50's between 1.04 µM and 2.9 µM were identified. These compounds were resynthesized but were found not to validate with the exception of one compound 2/MM1-19 from the Ugi series, albeit at 2-fold less activity than the hit (IC50 = 5.2 µM). The structure-activity relationship (SAR) based on this compound summarized in Figure 1 yielded compounds with abrogated antiplasmodium activity (IC50's >6 µM, which is the highest concentration tested in this assay). In addition to the aforementioned series, bacterial PPAT inhibitors reported by Novartis were explored, and a similar triazolopyrimidine series resulted in a hit compound 28/MM2-145 with PfNF54 IC50 = 2.2 µM. Formal hit assessment study of this compound with the SAR strategy proposed in Figure 2 resulted in compounds with low antiplasmodium activity. The Ugi series compound 2/MM1-19 and the triazolopyrimidine series compound 28/MM2-145 were found not to possess gametocytocidal activity when tested against the early and late-stage gametocytes. The compounds were also not found to be acting on the coenzyme A (CoA) biosynthesis pathway and thus unlikely inhibiting the PfPPAT when subjected to chemical rescue experiments in the presence of high concentration of metabolites of the pathway or the end-product CoA. The metabolomics data showed that compound 2/MM1-19 caused an increase in pyrimidine biosynthesis precursors N-carbamoyl-L-aspartate (N-Carb-Asp) and dihydroorotate (DHO) and a marked decrease in a number of peptides. 28/MM2-145 was found to cause an increase in pyrimidine biosynthesis precursors. The increase in pyrimidine biosynthesis precursors implicates pathways similar to those targeted by known antimalarials like atovaquone whose action is along the mitochondrial electron transport chain. Compound 2/MM1-19 did not inhibit -hematin formation (IC50 =1541 µM) as seen by decreased peptides in the parasite culture. In summary, the proposed PPAT inhibitors studied in this thesis were found to exhibit weak antiplasmodium activity and to be acting on different pathways beyond those involving Co-A biosynthesis. Penicillin binding protein (PBP) inhibitors from an antibacterial programme at H3D were screened for antiplasmodium activity. This identified a hit compound H3D006145 (43/MM2-92) with activity against PfNF54 (IC50 = 1.06 µM) and no cytotoxicity against Chinese Hamster Ovarian (CHO) and HepG2 cell lines at the highest concentration tested (IC50's >50 µM). A formal hit assessment was undertaken for this compound with the proposed SAR plan summarized in Figure 3. The SAR explorations showed that the methyl esters (PfNF54 IC50's between 0.4 and >6 µM) had better activity than the ethyl esters (PfNF54 IC50's between 1.21 and >6 µM) and the carboxylic acids were more active than the former two series (PfNF54 IC50's = 0.12–2.6 µM). These three series were all found to have no gametocytocidal activity against the early and late stages of gametocyte development and were noncytotoxic against mammalian CHO and HepG2 cell-lines at the maximum concentration tested (IC50's >50 µM). The investigation of the possible pathways targeted by this class of benzoxaboroles through metabolomics resulted in ambiguous metabolomic profiles which could not identify the exact metabolites resulting from the parasite treatment. Furthermore, the assessment of a selected representative analogue 45/MM2-91 for cross-resistance in a pool of barcoded resistant mutants with parasites resistant to known antimalarials and those in clinical development showed that the compound was not cross-resistant. This benzoxaboroles class was also found to have high in vitro microsomal stability when incubated with human, rat, and mouse liver microsomes with 91–99%, 90–99% and 87–97% of the compound remaining at 30 min, respectively. Retrospective rationalization of the binding mode in the editing domain of the P. falciparum LeucyltRNA (LeuRS) showed that these compounds have favourable interactions similar to previously reported related compounds. Lastly, the investigation of physicochemical properties determined both computationally and experimentally showed that the benzoxaborole series reported in this thesis possess drug-like characteristics. In conclusion, this study identified a new class of benzoxaboroles with sub-micromolar antiplasmodium activity and properties that supports its progression to a proof-ofconcept in vivo efficacy study in a mouse infection model.